Hackbuts from Chełm Town-Hall. A Contribution to Knowledge about Central-European Hand-Firearms in the 16th Century - Strzyż, Piotr; Dzieńkowski, Tomasz; Gołub, Stanisław (Acta Archaeologica Lodziensia, 2021)
Archaeological research on mediaeval and modern Chełm has been carried out for more than 100 years, but some particularly important information has been recovered in the last decade. Excavations have been carried out on the Cathedral mound, and likewise on the Old City on the settlement stretching from the 13th to the 20th century. In the year 2009 research was carried out in E. Łuczkowskiego Square, on the building which was the old Town Hall, whose beginnings stretch back to the 14th century or at least the beginning of the 15th. In one of the trenches two iron hackbuts were discovered. They were a type of hand-held firearm, in which the barrel was equipped with a vertical hook running downwards. They were used for the defence of town or castle walls. The archaeological context of the finds, as well as the diagnostic features of the hackbuts, point to a date in the 16th century, most probably in the first half. Considering the use to which these weapons report, however, they could have remained in use longer, until the 17th century. The find of the Chełm hackbuts allow us to compare them with other examples found in Central Europe.